Differentiated Learning Via Gallery Walk: Improving Pancasila Student Profiles and Learning Outcomes in Indonesian Elementary Education - Harmah Harmah; Supriadi Supriadi; Abdul Wahid (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Accommodating learner diversity under Indonesia’s Independent Curriculum (Kurikulum Merdeka) remains a persistent challenge, particularly in balancing cognitive competencies with the character-building dimensions of the Pancasila Student Profile (Profil Pelajar Pancasila, PPP). Conventional, lecture-centered instruction frequently fails to engage diverse learning styles or foster collaborative character formation. This Classroom Action Research (CAR) study investigated how integrating differentiated instruction with the Gallery Walk model enhances instructional quality, cognitive learning outcomes, and core PPP dimensions (cooperation, critical reasoning, and creativity). Following the Kemmis and McTaggart spiral model, the study was conducted over two reflective cycles with 23 fourth-grade students at Elementary School Inpres Lantebung, Makassar, Indonesia. Data were gathered using validated observation rubrics, PPP assessment instruments, and summative tests, and then analyzed through mixed descriptive methods. The results demonstrated substantial progress: the mean class score rose from a pre-cycle baseline of 64.35 to 73.91 in Cycle I, and 85.22 in Cycle II, yielding a 32.4% total gain. Classical mastery increased sharply from 30.43% to 69.60%, reaching 100% by Cycle II. Concurrently, PPP indicators advanced from